Si Juan tamad ay naging manghuhula Juan tamad became a seer - Vibiesca, Renato C. (Lampara books, 2009)
"The people in our village have many ways in doing things. On the other hand, Juan has a lot of excuses just to avoid work. He is called "Juan tamad" because he is just too lazy to do all tasks. One day, he makes his mother believe he is a seer-psychic. Find out in this story what Juan gets in return for pretending to be a seer-psychic."